Neuro-Fiqh and Premarital Counseling: A Neuroscience-Informed Framework for Strengthening Sakinah Family Development - Malik Ibrohim; Ishaq Ishaq; Wildani Hefni (Academia Open, 2026)
General Background: Contemporary Muslim societies face increasing marital instability marked by divorce, relational conflict, and emotional strain, highlighting the strategic role of premarital counseling in strengthening sakinah family development. Specific Background: Existing premarital programs within Islamic institutions predominantly emphasize legal rights, obligations, and doctrinal instruction grounded in Islamic family law (fiqh al-usrah), often with limited engagement with emotional regulation, attachment dynamics, and stress responses that shape marital interaction. Knowledge Gap: This imbalance reveals the absence of an integrative framework that systematically connects Islamic jurisprudential ethics with contemporary neuroscience to address psychological readiness prior to marriage. Aims: This study proposes Neuro-Fiqh as a conceptual framework that bridges fiqh-based ethical principles and neuroscientific insights to reformulate premarital counseling toward preventive and formative orientation. Results: Using qualitative library research and thematic integrative analysis of classical and contemporary fiqh literature, neuroscience, and family studies, the findings demonstrate strong conceptual compatibility between principles such as ḥusn al-muʿāsharah, darʾ al-ḍarar, ṣabr, masʾūliyyah, and neuroscientific mechanisms of emotional regulation, empathy, executive control, attachment security, and stress modulation. Novelty: Neuro-Fiqh positions neuroscience as an explanatory and pedagogical resource while preserving the normative and teleological authority of Islamic jurisprudence. Implications: This framework reconceptualizes premarital counseling as ethical–psychological formation, cultivating emotional awareness, moral accountability, and relational competence as foundations of sakinah family resilience and long-term family stability. Highlights: Jurisprudential marital ethics correspond closely with neural systems governing self-regulation, empathy, and stress processing. Integrative conceptual synthesis reorients marital preparation toward preventive and formative ethical development. The proposed model supports long-term household stability through cultivation of emotional and moral capacities prior to marriage. Keywords: Neuro-Fiqh, Premarital Counseling, Islamic Family Law, Neuroscience, Sakinah Family